Out-of-position telomeres in meiotic leptotene appear responsible for chiasmate pairing in an inversion heterozygote in wheat (Triticum aestivum L.) - Pernickova, Katerina; Linc, Gabriella; Gaal, Eszter; Kopecky, David; Samajova, Olga; Lukaszewski, Adam J (Chromosoma, 2019)
Chromosome pairing in meiosis usually starts in the vicinity of the telomere attachment to the nuclear membrane and congregation of telomeres in the leptotene bouquet is believed responsible for bringing homologue pairs together. In a heterozygote for an inversion of a rye (Secale cereale L.) chromosome arm in wheat, a distal segment of the normal homologue is capable of chiasmate pairing with its counterpart in the inverted arm, located near the centromere. Using 3D imaging confocal microscopy, we observed that some telomeres failed to be incorporated into the bouquet and occupied various positions throughout the entire volume of the nucleus, including the centromere pole. Rye telomeres appeared ca. 21 times more likely to fail to be included in the telomere bouquet than wheat telomeres. The frequency of the out-of-bouquet rye telomere position in leptotene was virtually identical to the frequency of telomeres deviating from Rabl's orientation in the nuclei of somatic cells, and was similar to the frequency of synapsis of the normal and inverted chromosome arms, but lower than the MI pairing frequency of segments of these two arms normally positioned across the volume of the nucleus. Out-of-position placement of the rye telomeres may be responsible for reduced MI pairing of rye chromosomes in hybrids with wheat and their disproportionate contribution to aneuploidy, but appears responsible for initiating chiasmate pairing of distantly positioned segments of homology in an inversion heterozygote.
Keywords: Heterozygote; Chimera; počítačové zpracování obrazu; Plant Cells; rostlinné buňky; párování chromozomů; Cell Nucleus; chiméra; In Situ Hybridization, Fluorescence; Triticum; Centromere; buněčné jádro; Chromosome Pairing; Chromosomes, Plant; Meiotic Prophase I; Microscopy, Confocal; profáze meiózy I; telomery; Species Specificity; heterozygot; druhová specificita; hybridizace in situ fluorescenční; žito; pšenice; centromera; zobrazování trojrozměrné; Secale; Imaging, Three-Dimensional; Chromosome Inversion; Telomere; konfokální mikroskopie; chromozomální inverze; chromozomy rostlin; Image Processing, Computer-Assisted